The social welfare function of forests in the light of the theory of public goods - János Seregi; Zsuzsanna Lelovics; László Balogh (Bamberg University, Bamberg Economic Research Group (BERG), 2012)
Differentiation between public and private goods is very complex and difficult. In this article, authors overview these definitions and also the theories about private and public goods to apply this knowledge in the determination of the social welfare functions of forests, the utilization and the tasks of the government. The welfare functions of forests, the tasks of the owner and also the way of utilization of the forest is differing between public and private forests. This overview can help to determine these functions and tasks and also find the best ways of utilization.
Keywords: 330; Social welfare; Private and public goods; Government